2014
DOI: 10.1016/j.pedhc.2012.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Treatment of Their Children's Pain at Home: Pharmacological and Nonpharmacological Approaches

Abstract: This study provides information that can help health care professionals initiate conversations regarding treatment options and align recommendations with techniques that parents are likely to use, and it can help health care professionals provide supportive alternative recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 63 publications
1
5
0
1
Order By: Relevance
“…Thus, parents may end up relying on their child's behavior. This study's results indicate that parents evaluate their child's pain intensity more often because of their own emotions, as shown in other studies (Caes et al, 2011; Gorodzinsky et al, 2014; Goubert et al, 2011; Vervoort et al, 2011). However, studies which report the difference in the evaluation of pain in children according to the child's age or gender are rare.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, parents may end up relying on their child's behavior. This study's results indicate that parents evaluate their child's pain intensity more often because of their own emotions, as shown in other studies (Caes et al, 2011; Gorodzinsky et al, 2014; Goubert et al, 2011; Vervoort et al, 2011). However, studies which report the difference in the evaluation of pain in children according to the child's age or gender are rare.…”
Section: Discussionsupporting
confidence: 85%
“…Children with negative pain memories had higher levels of anxiety and experienced more pain when they got older than those with positive pain memories (Noel, Chambers, McGrath, Klein, & Stewart, 2012a). All these indicate the need to empower parents with sufficient relevant knowledge and information via education to improve their abilities in caring for their child after the surgery (Gorodzinsky, Davis, & Drendel, 2014;Sandlin-Leming, 2010). However, very limited studies in the literature have reported the effects of educational interventions on parents' knowledge, attitudes and the use of pain relief methods that adopted a rigorous experimental design (Huth, Broome, Mussatto, & Morgan, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Gorodzinsky ve ark. 'ı ise bulgularımızdan farklı olarak ebeveynlerin çocuklarının ağrılarını hafifletmek için ağrı bölgesine buz uygulamasını sıklıkla yaptıklarını belirtti (Gorodzinsky et al, 2014).…”
Section: Discussionunclassified